Dubbel Spoor. (Heerlen : Stadsgalerij, 1992)
Leutscher, Hans ; de Zeeuw, Mirjam ; Boezem, Marinus ; Hocks, Teun ; Servaas ; Sherman, Cindy ; Pistoletto, Michelangelo ; Coehorst, Carolien ; Tuytel, Piet ; Green, Betsy ; Piene, Otto ; Merillon, George ; Warhol, Andy ; Dekkers, Ger ; Kruger, Barbara
Dubbel Spoor, Stadsgalerij, Heerlen, 12 juli t/m 13 september 1992
boek